The Genus Phytophthora (Peronosporales) in Argentina - Palmucci, Hemilse Elena (2020)
Background and aims: The genus Phytophthora includes plant pathogens that affect a wide host range and cause severe damage and economic losses. The aim of this study was to achieve a more comprehensive knowledge of Phytophthora in Argentina. To this end, a review was carried out from the first reports in the late nineteenth century until March 2019. M&M: Information was taken from printed and on-line primary and secondary sources such as Proceedings of National and International Scientific Meetings, Bulletins from National Institutions and Universities, periodical Journals, books and data bases, and then analyzed and categorized. Results: The revision allowed updating the status of Phytophthora species recorded in the country, considering their geographical distribution, groups of crops affected, host-pathogen relationships, symptoms and nomenclature changes, as well as presenting a quick and comparative access to different subjects related to these pathogens. The results showed that, to date, 20 Phytophthora spp., one species affinis and one taxon affect 223 host-pathogen relationships in Argentina. The diversity of Phytophthora species in the world suggests that a larger number of species, still not cited, could be present in Argentina. Conclusions: Researchers specialized in the genus Phytophthora, molecular techniques and phylogenetic studies, may allow progressing in the accurate identification of the species and knowledge of their genetic variability.